2017
DOI: 10.1093/jnci/djw317
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Isoform Ratio: A Breast Cancer Prognostic and Predictive Factor for Antiprogestin Responsiveness

Abstract: The PRA/PRB ratio is a prognostic and predictive factor for antiprogestin responsiveness in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 54 publications
5
66
0
1
Order By: Relevance
“…The staining was not homogeneous suggesting that the inducer is not equally distributed in the tumour. Figure 2A,B, and a PR negative breast cancer core, the three in the same TMA [3], is shown to reinforce the results shown in Figure 2A,B. The stained nuclei have been quantified as described in B.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The staining was not homogeneous suggesting that the inducer is not equally distributed in the tumour. Figure 2A,B, and a PR negative breast cancer core, the three in the same TMA [3], is shown to reinforce the results shown in Figure 2A,B. The stained nuclei have been quantified as described in B.…”
Section: Resultssupporting
confidence: 75%
“…The average number of positive nuclei with respect to total tumour cells in 10 different representative fields of T1 and T2 is shown in the adjacent bar charts (± SD). (C) IHC of T47D‐YA and ‐YB xenograft cores from a different experiment than those shown in Figure 2A,B, and a PR negative breast cancer core, the three in the same TMA , is shown to reinforce the results shown in Figure 2A,B. The stained nuclei have been quantified as described in B.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…PRBΔ4 mRNA expression has already been detected in breast cancer tissues. 35,36 Using selected human breast tumor samples from our tumor bank, 37 we show that the samples in which the intermediate band between PRB and PRA coincides with the PRBΔ4 band of T47D-Y PRBΔ4 transfected cells (Fig. 6a, right), also expressed PRBΔ4 mRNA (Fig.…”
Section: Prbδ4 Expression In Human Breast Cancermentioning
confidence: 89%
“…The increasing understanding of PR-A and PR-B as distinct, and even contradictory, growth regulators has encouraged the exploration of the role of the relative expression of PR-A and PR-B in cancer types such as EC 28 and breast cancer. 29,30 Jongen et al found shorter diseasefree survival and shorter overall survival for women with EC with a ratio of PR-A:PR-B < 1. The results of the present study demonstrated an 11-fold increased odds for relapse in women with pre-treatment PR-A:PR-B ≤ 1 compared with women with PR-A:PR-B > 1.…”
Section: Discussionmentioning
confidence: 99%